Karakteristik Healing Garden Taman Tiga Generasi Kota Balikpapan: Characteristics of the Healing Garden, Three Generations Park, Balikpapan City - Budiman, Deka Adam; Mustofa, Umar; Hidayat, Arief; Astha, Dwinsani Pratiwi (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2023)
Minister of Agrarian and Spatial Planning Regulation no. 14 of 2022 stipulates Public Green Open Space (RTH) as a place for plants in open spaces that can create a healthy city and improve community welfare. City parks, as one of the public open spaces, have an important role in reducing stress levels in urban communities. The city of Balikpapan will experience population growth of up to 6 thousand people in 2022, with a very high population density. This density can trigger stress. Healing gardens, or healing gardens, have the function of reducing stress levels, as proven in research by Setyani and Theresia. Balikpapan City's Three Generations Park, with an area of ​​1.5 hectares, is the focus of research as the largest active city park. Identifying the characteristics of the healing garden in this park is considered important to assess its effectiveness in reducing people's stress levels. The data collection method was carried out using a primary survey and the analysis used was explanatory qualitative descriptive. The findings are that there are 10 (ten) characteristics of a healing garden, namely soft/hard elements, accessibility, good views and bad views, lighting from sunlight and garden lights, smell, hearing, touch through therapeutic rocks and mattresses, security through fences and CCTV, peace and comfort.